2020
DOI: 10.1039/d0ta08101a
|View full text |Cite
|
Sign up to set email alerts
|

A photothermal and Fenton active MOF-based membrane for high-efficiency solar water evaporation and clean water production

Abstract: Solar-driven interfacial water evaporation (SDIWE) is a promising way to reduce the fresh water scarcity. However, it is still challenged to generate clean water from volatile organic compounds (VOCs) contaminated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Therefore, it is difficult to purify VOC-containing wastewater by SDIE. Ma et al 213 designed a PM (ZSG) with high Fenton catalytic activity. The high Fenton catalytic activity of ZSG promoted the generation of -OH, which degrades substances such as phenol of volatile organic solvents in situ, thereby helping to obtain clean fresh water.…”
Section: Volatile Organic Compound (Vos) Wastewatermentioning
confidence: 99%
“…Therefore, it is difficult to purify VOC-containing wastewater by SDIE. Ma et al 213 designed a PM (ZSG) with high Fenton catalytic activity. The high Fenton catalytic activity of ZSG promoted the generation of -OH, which degrades substances such as phenol of volatile organic solvents in situ, thereby helping to obtain clean fresh water.…”
Section: Volatile Organic Compound (Vos) Wastewatermentioning
confidence: 99%
“…2,3 Current technologies used in water puri-cation mainly depend on other water resources or expensive infrastructure, i.e., desalination, wastewater treatment and multi-stage ash distillation, and it is impractical to apply these technologies to produce clean water in desert areas. [4][5][6] In this regard, sorbent-based atmospheric water harvesting (AWH) exhibits great potential to provide potable water, as about 13 sextillion (10 21 ) L of water exists in air at any given time through the hydrological cycle. 3 Sorbent materials can spontaneously adsorb water and release it when energy is supplied.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the control of VOCs entering into condensed freshwater was achieved by photocatalysis, , additional oxidants, and membrane interception in the interfacial solar distillation process. For example, Song et al reported a dual-scale porous, photothermal/photocatalytic, flexible membrane for preventing VOCs from entering into the condensed freshwater during solar distillation; Shi et al reported the multifunctional honeycomb ceramic plates for the degradation of VOCs through the photo-Fenton reaction.…”
Section: Introductionmentioning
confidence: 99%